1992
DOI: 10.1128/jb.174.13.4427-4434.1992
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of corrinoids and factor F430 in the reductive dechlorination of 1,2-dichloroethane by Methanosarcina barkeri

Abstract: Cobalamin and the native and diepimeric forms of factor F430 catalyzed the reductive dechlorination of 1,2-dichloroethane (1,2-DCA) to ethylene or chloroethane (CA) in a buffer with Ti(III) citrate as the electron donor. Ethylene was the major product in the cobalamin-catalyzed transformation, and the ratio of ethylene to CA formed was 25:1. Native F430 and 12,13-di-epi-F430 produced ethylene and CA in ratios of about 2:1 and 1:1, respectively. Cobalamin dechlorinated 1,2-DCA much faster than did factor F430. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 49 publications
4
63
1
Order By: Relevance
“…3). In contrast to results obtained with 1,2-DCA, in which dechlorination by cobalamin and factor F430 took place at different rates (27), the formation of ethylene from BrES occurred at about the same rate (500 pmol/min/ nmol of catalyst) with either catalyst. Purified component C was also able to transform its own inhibitor BrES to ethylene (Table 3).…”
Section: Resultscontrasting
confidence: 44%
See 4 more Smart Citations
“…3). In contrast to results obtained with 1,2-DCA, in which dechlorination by cobalamin and factor F430 took place at different rates (27), the formation of ethylene from BrES occurred at about the same rate (500 pmol/min/ nmol of catalyst) with either catalyst. Purified component C was also able to transform its own inhibitor BrES to ethylene (Table 3).…”
Section: Resultscontrasting
confidence: 44%
“…When boiled cell extract was omitted, slow or no dechlorination was observed. The omission of component C already indicated that component A was not able to reduce free corrinoids and factor F430 present in boiled cell extract, which could also act as catalysts for dechlorination (27). Controls in which additional cobalamin or factor F430 was added in the absence of component C showed no dechlorination at all.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations